Coprecipitation with samarium hydroxide using multitracer produced through neutron-induced fission of 235U toward chemical study of heavy elements. (January 2022) - Kasamatsu, Yoshitaka; Nagase, Masahiro; Ninomiya, Hidemi; Watanabe, Eisuke; Shigekawa, Yudai; Kondo, Narumi; Takamiya, Koichi; Ohtsuki, Tsutomu; Shiohara, Naoya; Shinohara, Atsushi
Abstract: For new chemical studies on heavy elements, we previously investigated the coprecipitation behaviors with samarium hydroxide for various elements. Herein, we report the coprecipitation experiment using multitracer produced by neutron-induced fission of 235 U. The coprecipitation behaviors of 10 elements were investigated: new data were obtained for Sr, Ru, I, Pm, and Np. The present results support the previously obtained conclusion that the hydroxide precipitation properties of various elements can be qualitatively investigated through their coprecipitation behaviors. Graphical abstract: Image 1 Highlights: ● We identified 10 nuclides (10 elements) in multitracer produced by neutron-induced fission of 235 U. ● Coprecipitation behaviors of 10 elements with samarium hydroxide were simultaneously investigated using the multitracer. ● The hydroxide and ammine complex formations were investigated from the coprecipitation behaviors. ● The results support the establishment of a new experimental methodology for superheavy elements. ● The established method will lead to the study on various precipitates of superheavy elements.